Pengaruh Semangat Kerja Dan Pengawasan Terhadap Loyalitas Pegawai Dinas Tenaga Kerja Dan Transmigrasi Kabupaten Labuhanbatu Utara - Raja Saul Marto Hendry (LPPM Universitas Labuhanbatu, 2021)
Currently there are still many employees who do not have the spirit of work and the spirit of work and do not really like the supervision of performance conducted by the organization where he works so that many employees who do their jobs in a hurry and not conscientious yag can lead to decreased performance in the organization which ultimately have a negative ; 2) to determine the relationship of supervision of loyalty to the Financial Management Agency and labuhabatu regional assets; 3) to determine the relationship of motivation, and simultaneous or joint supervision of loyalty to the Financial Management Agency and labuhabatu regional assets. Â Â This study is a study with probability sampling or sample available that as many as 66 samples of respondents from a total population of 80 employees determined using slovin formula with an error rate of 5%. This Data is processed using SPSS ( Statistical product and service solution ). The results showed that partially morale has a significant positive influence on loyalty with significan (0.000 < 0.05); supervision has a significant positive influence on semagat work with significant (0.000 <0.05); simultaneously or together variable morale and supervision has a significant positive influence on loyalty with significa (0.000 <0.05).Â